Perkembangan Morfologi dan Tingkah Laku Larva Ikan Tuna Sirip Kuning Yellowfin Tuna (Thunnus albacares) - Asri, Yuliana; Muahiddah, Nuri (LPPM Universitas Mataram, 2024)
The yellowfin tuna (Thunnus albacares) is a pelagic fish with distinct morphological development and behavioral traits. Understanding the early stages of morphology and behavior in yellowfin tuna larvae is crucial for successful cultivation efforts, particularly during the hatchery phase. This study aimed to observe and document the developmental progression and behaviors of yellowfin tuna larvae at the Tuna Laboratory of Balai Besar Riset Budidaya Laut and Penyuluhan Perikanan Gondol, Bali. Yellowfin tuna larvae were reared in 700 L round tanks at a density of 10,000 larvae per tank. Larval rearing was monitored over a period of 13 days, specifically on days 1 (D1), 3 (D3), 5 (D5), 7 (D7), 10 (D10) and 13 (D13) post-hatching. Morphological changes in the larvae were observed over time. On day 1, the larvae were transparent and planktonic, with closed mouths and eyes and the presence of melanophore pigments in their bodies. By day 3, the larvae had opened their mouths and eyes, becoming capable of feeding. The mouth opening measured between 0.34-0.68 mm (90Â°) and 0.18-0.37 mm (45Â°) on day 5 post-hatching. As the larvae grew, improvements in swimming ability were noted, correlating with the development of the swim bladder, tail fin, and dorsal fin.